DIY music and the politics of social media - Jones, Ellis Nathaniel (Bloomsbury Academic, 2021)
The Problem? : Welcome to the democratic, DIY music business -- The Past : DIY, popular music, and cultural resistance -- The Personal : Subjectivity and self-representation on social media -- The Players : Hierarchy, ownership, and collectivism in DIY scenes -- The Public : Performing politics and elucidating difference -- The Popular : Metrics, measurements, and the DIY imagination -- The Platform : Alterity and the political economy of social media -- The Plan... : Potential futures for DIY music, new media, and social justice
Includes bibliographical references
Keywords: Popular music / Social aspects; Music trade / Social aspects; Social media; Music industry